Computer-based crime incident reporting and monitoring system at headquarters Philippine Constabulary level - Ponteres, Imelda C.; Kanchit Malaivongs; Huynh, Ngoc Phien; Overby, Magnus B.; US-ASEAN (Bangkok : Asian Institute of Technology, 1985)
The study aims to design an information system for the Philippine Constabulary - Integrated national Police to handle its functions of reporting and monitoring crime incidents at the Headquarters level. It is directed towards developing an integrated system to be used by all law enforcement agencies in the country. As such, the Crime Incident Reporting and Monitoring System (CIRMS) is designed to have the following capabilities: on-line data recording and updating. report generation, query facility, controlled access to the database, validation controls to maintain data integrity and standardized input procedures to reduce data redundancy. Data elements to be stored are determined through the normalization process and these are documented in a data dictionary. The proposed conceptual CIRMS Model consists of new input forms. report formats, screen formats for the queries, process structures, information flow and activity procedures. Space requirements is determined based on the annual crime volume and corresponding relational volume as defined in the data model. This requires that the system is to be implemented on a large computer and consequently, to achieve the objectives set for the development of the system, a DBMS must be used. For the purpose of proving the correctness of analysis and design of the CIRMS, a prototype is developed through the use of high-level languages, UNIQUE-II and UNIQUE-RG, and a DBMS software, SIBAS, in the Norsk Data Computer. The prototype demonstrates the functional aspects of the proposed system in terms of maintenance of the CIRMS database, generation of reports and processing of inquiries.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1985
Keywords: Crime and criminals -- Philippines -- Data processing